1989
DOI: 10.1159/000125197
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Adrenocorticotropic Hormone in the Rat Demonstrates Three Different Rhythms within 24 h

Abstract: Secretion of adrenocorticotropic hormone (ACTH) by the anterior pituitary is rhythmic and episodic, as reflected by fluctuations in plasma concentrations of ACTH. The present work was designed to further characterize the patterns of ACTH secretion that occur simultaneously within a 24-hour period in the rat. To accomplish this, blood collection protocols with sampling intervals of 2 min, 15 min, and 4 h were used in awake, chronically cannulated rats. Plasma samples were assayed for immunoreactive ACTH, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 28 publications
4
40
0
Order By: Relevance
“…In this respect, it is remarkable that both GRP and VIP (i.e., two peptidergic transmitters contained in SCN neurons) exhibit ACTH and corticosterone release stimulating properties (Gunion et al, 1989;Olsen et al, 1992;Alexander and Sander, 1994). The early onset of the stimulatory SCN input (i.e., between CT2 and CT6), as revealed by our timed VP antagonist infusions, would agree with the often-reported phaseadvanced rhythms of CRH and ACTH compared with that of corticosterone (Szafarczyk et al, 1980;Graf et al, 1988;Carnes et al, 1989;Owens et al, 1990;Kwak et al, 1992;Cai and Wise, 1996) and the elevated daytime levels of GRP mRNA in the SCN (Zoeller et al, 1992;Inouye et al, 1993;Inouye and Shibata, 1994). Because VP-, VIP-, and GRP-containing SCN fibers display clearly separated innervation patterns of the PVN/DMH subdivisions (Buijs et al, 1993b;Kalsbeek et al, 1993), a differentiated control of ACTH and corticosterone release by SCN efferences is certainly possible.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this respect, it is remarkable that both GRP and VIP (i.e., two peptidergic transmitters contained in SCN neurons) exhibit ACTH and corticosterone release stimulating properties (Gunion et al, 1989;Olsen et al, 1992;Alexander and Sander, 1994). The early onset of the stimulatory SCN input (i.e., between CT2 and CT6), as revealed by our timed VP antagonist infusions, would agree with the often-reported phaseadvanced rhythms of CRH and ACTH compared with that of corticosterone (Szafarczyk et al, 1980;Graf et al, 1988;Carnes et al, 1989;Owens et al, 1990;Kwak et al, 1992;Cai and Wise, 1996) and the elevated daytime levels of GRP mRNA in the SCN (Zoeller et al, 1992;Inouye et al, 1993;Inouye and Shibata, 1994). Because VP-, VIP-, and GRP-containing SCN fibers display clearly separated innervation patterns of the PVN/DMH subdivisions (Buijs et al, 1993b;Kalsbeek et al, 1993), a differentiated control of ACTH and corticosterone release by SCN efferences is certainly possible.…”
Section: Discussionsupporting
confidence: 83%
“…Contrary to the corticosterone data, ACTH levels showed no diurnal variation during the different Ringer's infusions ( p Ͼ 0.5), although variability during the CT10 experiment was considerably higher than at any other time of the day (16.8 Ϯ 2.8 vs 6.8 Ϯ 1.9, 7.6 Ϯ 2.3, 10.6 Ϯ 1.1, and 11.0 Ϯ 2.4 pg/ml). A number of previous studies have reported diurnal variations in plasma ACTH levels Carnes et al, 1989;Bagdy et al, 1991;Kwak et al, 1992;Ixart et al, 1993), but quite a few others failed to detect significant diurnal variations (Wilkinson et al, 1979;Akana et al, 1986;Carnes et al, 1986;Cascio et al, 1987;Kwak et al, 1993;Suemaru et al, 1995). Important factors that may contribute to the difficulty of finding a circadian ACTH rhythm are the low amplitude of the rhythm, the episodic secretion of ACTH, the sampling protocol used (Carnes et al, 1986;Turek and Van Cauter, 1988;Carnes et al, 1989), and the assay variability (e.g., CT times in different assays).…”
Section: Discussionmentioning
confidence: 99%
“…ACTH is also released in a pulsatile manner in the rat (Carnes et al 1989), and shows a diurnal rhythm albeit with an amplitude which is considerably lower than that of corticosterone (Dallman et al 1978, Kaneko et al 1980, 1981. Unfortunately due to the large sample volumes needed for the assay of ACTH, we were limited in the frequency and duration of samples we were able to perform and thus we could not investigate the effect of Org on ACTH pulsatility or diurnal rhythm.…”
Section: Effect Of the V 1b R Antagonist Org On Basal Pituitary-adrenmentioning
confidence: 98%
“…However, diurnal fluctuations in plasma ACTH are of low amplitude and are frequently not significant over a 24-h period (27), so that amplification of this rhythmic signal is necessary to yield a pronounced adrenal rhythm. It has been shown in rats that such an amplification is provided by an increased adrenal sensitivity to ACTH at the peak of the corticosterone (CORT) rhythm, i.e., at lights off in nocturnal rodents (6,7,9,25,34).Several studies collectively showed that diurnal changes in adrenocortical sensitivity occurred independently of changes in ACTH. The first demonstration was provided by Dallman et al (9), who observed, under resting conditions, a persistent adrenal rhythm in dexamethasone-treated rats with no ACTH rhythm and, conversely, persistent diurnal ACTH fluctuations in the absence of adrenal rhythm after treatment with parachlorophenylalanine.…”
mentioning
confidence: 99%